Let's lock them in: Collusion under consumer switching costs - Niklas Fourberg (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2018)
Consumer switching costs cause the market demand of consumers who already bought a supplier's product to be less elastic while they simultaneously increase competition for new consumers. I study the effect of this twofold pricing incentive on firms' price setting behavior in a 2x2 factorial design experiment with and without communication and under present and absent switching costs. For Bertrand duopolies consumer switching costs reduce the price level vis-à-vis new consumers but do not affect price levels towards old consumers. Markets are overall less tacitly collusive which translates into higher incentives to collude explicitly. Text-mining procedures reveal linguistic characteristics of the communicated content which correlate with market outcomes and communication's effectiveness. The results have implications for antitrust policy, especially for the focus of cartel screening.
Keywords: C7; C9; L13; L41; 330; Switching Costs; Cartels; Collusion; Experiments